Fabric of India life: The 2006-2007 Fulbright experience - Hawley, Jana M. (My University, 2009)
Delicate and colorful Indian fabrics have penetrated the global marketplace for centuries. This article describes the Fabric of Indian Life Fulbright experiences of the 20 members who traveled throughout Northern India for one month, immersed in Indian culture with a focus on the textiles.
Keywords: India; Textiles; Culture; Fulbright project; Clothing trade